A Model of Sky Temperature Estimation at 1.42 GHz using University of Baghdad’s Radio Telescope - Hameed, Ahmed A.; Abood, Kamal M. (Iraqi Journal of Science, 2021)
The objective of this study is to select a suitable observing region at Baghdad location (44o 22’ 48", 33o 16’ 30") with low interference that may affect frequency of 1.42 GHz. Baghdad University Radio Telescope (BURT) is used in this study to determine a convenient region for observation in Baghdad sky. Different azimuths and elevations were chosen at different observations time. The results of this study showed that the best observations regions were located at azimuth (120o-160o) and (210o-260o). These regions included less sky temperature and estimated to be (42.8 to 163) K. The sky temperature model could be represented as a polynomial of third degree that could fit the behavior of the observation points.